IMAGINING JUSTICE: THE POLITICS OF POSTCOLONIAL FORGIVNESS AND RECONCILIATION - McGonegal, Julie (My University, 2004)
Possibly owing to a spirit of millenarianism, discourses of forgiveness and reconciliation have emerged as powerful scripts of interracial and interethnic negotiation in states struggling with the legacies of colonialism. This study examines the representation and production of these discourses in contemporary fiction by J.M. Coetzee, Joy Kogawa, David Malouf, and Michael Ondaatje. It argues that although they disconcel1 or stupefy critics situated in postmodern contexts, the rhetoric and rituals that structure reconciliation processes may be crucial to a departure from colonialist and racist relations, and to the commencement of a more democratic future. Using a postcolonial methodology, Imagining Justice challenges assumptions that discourses of forgiveness and reconciliation necessarily entail a rush to closure, repression of memory, or recuperation by power. Ultimately it suggests that if the prerogative of oppressed groups to devise their terms is conceded, forgiveness and reconciliation may render radical revision to prevailing systems of violence and injustice imaginable.
Keywords: English Language and Literature; English Language and Literature